Sejarah Perjuangan Rakyat Solor Melawan Portugis Di Kesultanan Menanga Tahun 1613-1645 - Muhammad, Mufidah; Djakariah, Djakariah; Dethan, Delsy A (FLORESIENSIS, 2022)
The purpose of this study is to find out the history of the Portuguese entry into Solor in 1561, the background of the resistance of the Solor people against the Portuguese in 1613-1645, and the course of the resistance between the Solor people and the Portuguese in 1613-1645. This study uses historical methods. The results of this study show that (1) The history of the Portuguese entry into Solor Lohayong in the 16th century AD (1561). (2) the background of the resistance of the Solor people against the Portuguese in 1613-1645 includes 3) The course of the resistance of the Solor people against the Portuguese in 1613-1645.